Potential mechanisms responsible for occurrence of core oxygen minimum zone in the north-eastern Arabian Sea. (November 2020) - Sarma, V.V.S.S.; Bhaskar, T.V.S. Udaya; Kumar, J. Pavan; Chakraborty, Kunal
Abstract: The thickness of oxygen minimum zone (OMZ) is estimated for the first time using dissolved oxygen (DO) profiles obtained from the Biogeochemical Argo floats collected between 2013 and 2019 in the Arabian Sea. The depth of upper boundary of the OMZ varied narrowly between 70 and 220 m in the entire Arabian Sea whereas the lower boundary of OMZ significantly deepened from south (500 m) to northern Arabian Sea (1200 m). The thickness of OMZ decreased from north (>1050 m) to south (400 m) with the thickest OMZ in the northeastern Arabian Sea (950–1050 m). The thick OMZ in the northeastern Arabian Sea is associated with low concentration of depth integrated Chlorophyll-a, primary production in the upper 100 m and sinking carbon fluxes at 100 m depth than other regions. The particle back-scatter, proxy for particulate organic matter, is higher in the northeastern than other regions in the Arabian Sea. The high particle back-scatter data is found in the core of OMZ and it is increased from shelf to offshore indicating that cross-shelf transport of organic matter may be supporting bacterial carbon demand in the OMZ in the northeastern Arabian Sea. The eastward shift in the OMZ is attributed to weak mixing, high penetration time of intermediate water masses, and organic matter transport from the shelf region. Numerical models estimated negligible changes in DO in the OMZ since past several decades, whereas long-term observational data indicates decline in DO levels in the OMZ. Such contrasting results may be caused by lack of cross-shelf transport of organic matter in the models. Though this study identifies the occurrence of cross-shelf transport, the nature, quality and composition of organic matter transported from shelf is unknown. Nevertheless, inclusion of such processes in the models may improve predictability of possible changes in OMZ in future in the Arabian Sea. Highlights: The lower boundary of the oxygen minimum zone (OMZ) is deeper in the northern compared to southern Arabian Sea. Thicker OMZ exists in the northeastern Arabian Sea (NEAS) associating with low primary and export production. Organic matter transport from the shelf may support bacterial organic carbon demand in the OMZ in the NEAS. Plankton composition, sinking fluxes, cross-shelf transport of organic matter controls occurrence of intense OMZ in the NEAS.